IMPLEMENTASI PEMBELAJARAN IPA BERBASIS PROYEK MELALUI PENDEKATAN INQUIRY DAN MODEL KOOPERATIF STAD UNTUK MENGEMBANGKAN KOMPETENSI KEWIRAUSAHAAN SISWA - Desianto; Siti Sarah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Science learning in elementary schools often does not provide adequate opportunities for developing 21st-century competencies, including entrepreneurial skills that require creativity, collaboration, and problem-solving abilities. A similar condition was found at SD Negeri 1 Ajibarang Wetan, where instruction remains teacher-centered and has not fully utilized project-based learning that integrates scientific processes with entrepreneurial character formation. This study aims to describe the implementation of project-based science learning through the Inquiry approach and the STAD cooperative model, as well as to explore its contribution to developing students’ entrepreneurial competencies. This research employed a descriptive qualitative approach. Data were collected through participatory classroom observations, in-depth interviews with teachers and students, and documentation of project products and field notes. Data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings indicate that embedding Inquiry within project activities encourages students to develop curiosity, question formulation skills, critical thinking, and creativity in producing scientific products. The use of the STAD model within heterogeneous teams strengthens students’ communication, collaboration, responsibility, and collective problem-solving. The study reveals that project-based science learning that integrates Inquiry and STAD effectively fosters entrepreneurial competencies such as creativity, innovation, initiative, risk-taking, and teamwork. The implications highlight the necessity for elementary schools to broaden the implementation of Inquiry-oriented and cooperative project-based learning to promote entrepreneurial character formation from an early age.